A Critical Discourse Analysis of the Portrayal of Climate Change in Pakistani English Newspapers’ Headlines - Hazaima Aslam; Dr. Asma Kashif Shahzad (Corresponding Author) (`, 2025)
Climate change has emerged as a major global issue in this century, impacting the environment, society, the economy, and politics. Although scientists agree on its causes, most people’s perceptions and policies are influenced by media portrayals of the phenomenon. This study investigates how climate change is depicted in leading Pakistani English newspapers. Five samples from Dawn are analyzed. Using Norman Fairclough’s three-dimensional model of Critical Discourse Analysis (1992), the study reviews various headlines from these articles. It examines how word choices, metaphors, and references to earlier texts communicate specific messages, assign responsibilities, and shape public perceptions of environmental issues. The research explores how lexical choices, metaphorical framing, and intertextual references create particular meanings, distribute responsibilities, and influence perceptions of ecological crises. Findings indicate that discussions about climate change are often shaped by government beliefs, Pakistan’s economic development plans, and international opinions. Often, climate change is framed as a result of disasters like floods and heatwaves rather than as a policy or sustainability issue. Keywords: Critical Discourse Analysis, Portrayal, Climate Change, Pakistani English Newspapers’ Headlines.